Ethnic Differences and the Closing of the Sex Gap in Alcohol Use Among College-Bound Students - Corbin, William R. (2008)
In this study, the authors used Web-based surveys to examine differences in alcohol use by sex and ethnicity and factors associated with these group differences among 2,241 college-bound students. A Sex × Ethnicity interaction indicated that the sex gap was much larger for Latino than for Caucasian students. Although peer influence was important for both Caucasian and Latino students, family influences were significant only for Latino youths. The sex differences in drinking among Latino youths were largely explained by the combination of same-sex family member and same-sex peer drinking through values about the acceptability of drinking behavior. Among Caucasians, perceptions of peer behavior exerted a stronger influence on drinking behavior than among Latinos. These results suggest that interventions targeting peer influence are likely to be most effective for Caucasian students. In contrast, for Latinos, particularly Latina women, family characteristics may be an important target for prevention.